(untitled) (Journal of Plant Disease Sciences, 2018)
Six fungitoxicants were evaluated against Cladosporium carpophilum causing scab in almond. Fungitoxicants proved significantly effective as compared to check. The minimum leaf scab intensity of 1.92 per cent and twig intensity 2.48 per cent as compared to check (26.35 and 28.92 %, respectively) were recorded where copper oxycholoride50 WP (0.3%) applied at dormant stage beside carbendazim 50WP(0.05%) , chlorothalonil 75 WP (0.3%) , difenaconazole 25 EC (0.03%), captan 50 WP (0.3%) and pyraclostrobin 60 WG (0.025%) applied at pink bud, petal fall, fruitlet, 15 days after fruitlet and 30 days after fruitlet stages, respectively. Maximum leaves scab intensity of 16.83 per cent and twig intensity of 18.37 per cent were recorded in treatment of carbendazim 50WP (0.05%) , chlorothalonil 75 WP(0.3%) and difenaconazole 25 EC(0.03% were applied at respective phenological stages.